Saturation estimation with complex electrical conductivity for hydrate-bearing clayey sediments: an experimental study - Xing, Lanchang; Zhang, Shuli; Zhang, Huanhuan; Wu, Chenyutong; Wang, Bin; Lao, Liyun; Wei, Wei; Han, Weifeng; Wei, Zhoutuo; Ge, Xinmin; Deng, Shaogui (Springer, 2024)
Clays have considerable influence on the electrical properties of hydrate-bearing sediments. It is desirable to understand the electrical properties of hydrate-bearing clayey sediments and to build hydrate saturation (Sh) models for reservoir evaluation and monitoring. The electrical properties of tetrahydrofuran-hydrate-bearing sediments with montmorillonite are characterized by complex conductivity at frequencies from 0.01 Hz to 1 kHz. The effects of clay and Sh on the complex conductivity were analyzed. A decrease and increase in electrical conductance result from the clay-swelling-induced blockage and ion migration in the electrical double layer (EDL), respectively. The quadrature conductivity increases with the clay content up to 10% because of the increased surface site density of counterions in EDL. Both the in-phase conductivity and quadrature conductivity decrease consistently with increasing Sh from 0.50 to 0.90. Three sets of models for Sh evaluation were developed. The model based on the Simandoux equation outperforms Archie’s formula, with a root-mean-square error (ERMS) of 1.8% and 3.9%, respectively, highlighting the clay effects on the in-phase conductivity. The frequency effect correlations based on in-phase and quadrature conductivities exhibit inferior performance (ERMS = 11.6% and 13.2%, respectively) due to the challenge of choosing an appropriate pair of frequencies and intrinsic uncertainties from two measurements. The second-order Cole-Cole formula can be used to fit the complex-conductivity spectra. One pair of inverted Cole-Cole parameters, i.e., characteristic time and chargeability, is employed to predict Sh with an ERMS of 5.05% and 9.05%, respectively.
Keywords: gas hydrate; complex electrical conductivity; hydrate-bearing clayey sediment; hydrate saturation; Simandoux equation; frequency dispersion; Cole-Cole formula